2021
DOI: 10.3390/pharmacy9040196
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Enhanced Palliative Care Pharmacy Service during the Initial COVID-19 Surge

Abstract: The Northern Health and Social Care Trust developed an enhanced palliative care pharmacy service for acute inpatients within a large hospital in Northern Ireland during the initial COVID-19 surge. By training additional staff, there was an opportunity to increase service provision, utilising palliative care pharmacy skills to undertake activities such as the symptom management of patients, appropriate management of medicines, improved access to medicines, advice for other healthcare professionals, and supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The others sources originated from the United Kingdom (n = 3/22, 13.6%), Poland (n = 1/22, 4.5%), and Qatar/Canada (n = 1/23, 4.5%). The majority of the included articles (n = 12/22, 54.5%) were original articles [ 21 , 32 42 ], followed by articles classified as practice reports (n = 6/22, 27.3%) [ 43 – 48 ] and practice research reports (n = 4/22, 18.2%) [ 26 , 49 – 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The others sources originated from the United Kingdom (n = 3/22, 13.6%), Poland (n = 1/22, 4.5%), and Qatar/Canada (n = 1/23, 4.5%). The majority of the included articles (n = 12/22, 54.5%) were original articles [ 21 , 32 42 ], followed by articles classified as practice reports (n = 6/22, 27.3%) [ 43 – 48 ] and practice research reports (n = 4/22, 18.2%) [ 26 , 49 – 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, only five reported measurable impacts on clinical outcomes. Five articles reported findings from cost analyses (see Table 2 ) with all demonstrating an association between the provision of pharmacy services and potential cost savings [ 26 , 33 , 35 , 37 , 51 ]. One of these articles showed that there was no significant association between the time spent by the pharmacist performing services and the number of medication requirements and per diem medication costs, regardless of the pharmacist chosen by the hospices (prescription benefits manager, pharmacist on staff or both) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, pharmacists contribute to the provision of palliative care in hospices and hospitals [51].…”
Section: Pharmaceutical Care Services In the Hospital Pharmacy Settingmentioning
confidence: 99%
“…Introdução: A satisfação dos utentes é um importante resultado para avaliar os aspetos dos serviços que carecem de melhorias (Hanley et al, 2021). No contexto da farmácia, a avaliação da satisfação tem sido conduzida por meio do uso do Pharmacy Services Questionnaire (PSQ) bidimensional, com 20 itens e categoria de resposta na escala de Likert até 5 pontos (Larson et al, 2002).…”
Section: Introductionunclassified